Optimal Contracts with Lock-In - Farrell, Joseph; Shapiro, Carl (American Economic Review, 1989)
We analyze incomplete long-term bilateral contracts when buyers incur relationship-specific setup costs and sellers choose some aspect of quality that is not verifiable to third parties. If setup costs are observable, the first best can be achieved even though contracts cannot enforceably specify quality; this does not even require long-term contracts. If setup costs are unobservable, however, then long-term price contracts can outperform short-term contracts, although they are not constrained Pareto efficient.